The Role of Law in International Business Transactions in the Era of Free Trade - Gunawan, Syahrana Kezia Anjunien (JURNAL MAHASISWA YUSTISI, 2025)
International trade is currently undergoing very significant progress, in line with the progress of the era of globalization. This condition allows people to meet their living needs not only from local sources, but also from various regions abroad. These developments provide the flexibility for the global community to choose trading partners and resources that it considers capable of meeting its needs. In this context, the role of law is vital in regulating cross-border business transactions, in order to ensure legal certainty, safeguard the rights and obligations of each party, and prevent legal conflicts from arising. Based on this, this study is intended to examine how the law plays a role in regulating trade flows through international business transactions in the midst of the era of free trade. The approach used in this study is the normative juridical method, which is a research method that focuses on the analysis of legal materials through literature studies. The legal sources used include laws and regulations, court decisions, and legal literature that is relevant to the subject of discussion. The principle of freedom in international trade must remain within the general legal framework that is the basis for the drafting of international contracts. Although the law governing international business transactions is included in the category of private law that gives the parties the flexibility to formulate the content of the agreement according to their respective interests, the transaction must still be subject to the provisions of international law and pay attention to the national legal regulations of each country involved. Thus, a deep understanding of the legal aspects of international business transactions is very important for business actors, so that they are able to adapt and compete optimally in the dynamics of the global market.